Magic lessons - Hoffman, Alice 1952- (Simon & Schuster, 2020)
"In an unforgettable novel that traces a centuries-old curse to its source, beloved author Alice Hoffman unveils the story of Maria Owens, accused of witchcraft in Salem, and matriarch of a line of the amazing Owens women and men featured in Practical Magic and The Rules of Magic"--
Prequel to Hoffman's 1995 book, Practical magic
Keywords: Abandoned children / Fiction; Witches / Fiction; Magic / Fiction; Blessing and cursing / Fiction; Family secrets / Fiction; British / Massachusetts / Salem / Fiction; Salem (Mass.) / History / Colonial period, ca. 1600-1775 / Fiction; FICTION / Literary; FICTION / Historical / General; FICTION / Occult & Supernatural; British; Abandoned children; Blessing and cursing; Family secrets; Magic; Witches; Massachusetts / Salem; Women / Fiction; Salem (Mass.) / History / Fiction; 1600-1775; Fantasy fiction; Fiction; Historical fiction; History; Paranormal fiction; Occult fiction; Fiktionale Darstellung